1991
DOI: 10.1002/pssb.2221640104
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Investigation about the “F” Centre in MeF2:A+ (MeCa, Sr; ALi, Na, K)

Abstract: One of the most conspicuous colour centres in MeF, : A + (Me = Ca, Sr; A = Li, Na, K) is the so-called "Fe:,".It is investigated whether this centre may really be composed of three neighbouring fluorine vacancies, along a [0, 0, 11 direction, decorated by two electrons, with an alkaline impurity A + in the vicinity. This structure seems to be ruled out by a comparison of the experimental magnetic circular dichroism data of other authors with the results of present Hartree-Fock calculations of the energy levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This was attributed to the R þ A centre (also represented as F þ 3a centre) having a linear structure on the basis of polarization luminescence. Based on the results of magnetic circular dichroism and a suitable theoretical model it was suggested that the R þ A centre should have angular configuration rather than linear one [25]. Thus, the true structure of the centre giving rise to the absorption at 2.53 eV and emission at 2.23 eV is debatable.…”
Section: Article In Pressmentioning
confidence: 99%
“…This was attributed to the R þ A centre (also represented as F þ 3a centre) having a linear structure on the basis of polarization luminescence. Based on the results of magnetic circular dichroism and a suitable theoretical model it was suggested that the R þ A centre should have angular configuration rather than linear one [25]. Thus, the true structure of the centre giving rise to the absorption at 2.53 eV and emission at 2.23 eV is debatable.…”
Section: Article In Pressmentioning
confidence: 99%